Efficiency Enhancement of Chlorine Contact Tanks in Water Treatment Plants: A Full-Scale Application - Kizilaslan, M. Anil; Demirel, Ender; Aral, Mustafa M. (Mdpi, 2019)
The mixing and disinfection performance of a full-scale chlorine contact tank (CCT) is thoroughly investigated by means of numerical simulations for seasonal water supply variations in the water treatment plant (WTP) of Eskisehir in Turkey. Velocity measurements and tracer studies are carried out on a 1:10 scale laboratory model of the CCT to validate the numerical model. A good agreement between numerical and experimental results shows that the numerical model developed can be reliably used for the simulation of turbulent flow and solute transport in the full-scale CCT. Tracer studies indicate that the hydraulic performance of the CCT is classified as average according to the baffling factor, while the Morrill, Aral-Demirel (AD), and dispersion indexes indicate low mixing due to the recirculating and short-circuiting effects inside the chambers of the CCT. With respect to the first order modeling of chlorine decay and pathogen inactivation, chlorine concentrations are found to be significantly distinct for seasonal variations in water supply to maintain 3-log inactivation of Giardia cysts. A recently developed and patented slot-baffle design (SBD) is then applied to the full-scale CCT. It is found that the hydraulic efficiency of the CCT is improved to high and the Morrill index approaches 2, which identifies the system as a perfect mixing tank. Using the SBD, the chlorine demand has been successfully decreased by 19% while providing equivalent inactivation level. The novel SBD design also reduces energy loses in the turbulent flow through the tank and increases the energy efficiency of the CCT by 62%, which is significant for energy considerations in modern cities.
Keywords: Chlorine Contact Tank; Disinfection Efficiency; Efficiency Enhancement; Computational Fluid Dynamics (Cfd); Pathogen Inactivation; Ct Concept